Spatiotemporal evolution characteristics and deformation mechanism of Suijiang landslide in Xiangjiaba reservoir, China - Wenping Dong; Fengyuan Wan; Jinyu Dong; Fuchu Dai (Scientific Reports)
Abstract In September 2013, the third phase of impoundment of the Xiangjiaba Hydropower reservoir to 380 m was conducted. In July 2014, large numbers of cracks appeared in many parts of Suijiang landslide seriously threatening the safety of 4300 residents. Understanding the spatiotemporal evolution characteristics of the landslide and analyzing the deformation mechanism could help in evaluation of the stability and prevent secondary disasters. On the basis of detailed geological survey data, monitoring data, and spatiotemporal evolution characteristics, this study comprehensively analyze the deformation mechanism and propose a new conceptual model of the Suijiang landslide in Xiangjiaba reservoir, China. This study concludes that the backfilling of the L gully blocked the drainage blind ditch such that the groundwater level of the entire slope was elevated, which was the main triggering factor. As the rainfall increased, the rate of deformation also increased, and the greatest deformation corresponded to the annual occurrence of the rainy season, which is the main influencing factor of deformation. The reservoir water level was a secondary influencing factor. The abrupt drop in reservoir water level had a greater impact on deformation compared with that of a rise in reservoir water level. Influenced by differences in consolidation characteristics caused by uneven backfilling of the L gully, the filling area produced deformation firstly. The rear part forms “active force transfer area” and the resistant-sliding zone forms “passive extrusion area”. The Suijiang landslide showed a sliding mode of “creep pushing-bending bedding shearing”. The slope continues to deform affected by external factors. It is suggested that further resistant-sliding measures will be incorporated to control further development and improve stability.